2011
DOI: 10.1002/ijc.25976
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase‐2 inhibition causes antiangiogenic effects on tumor endothelial and vascular progenitor cells

Abstract: Tumor angiogenesis is necessary for solid tumor progression and metastasis. Cyclooxygenase (COX)-2 is known to play an important role in cancer growth and invasion, and it activates the signaling pathways controlling cell proliferation, migration, apoptosis, and angiogenesis. COX-2 is reported to be expressed in many cancer cells. Several studies have reported successful treatment of cancer cells with COX-2 inhibitors (COX-2is). However, the effect of COX-2 inhibition on the tumor endothelium remains to be elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 45 publications
3
65
0
1
Order By: Relevance
“…Upregulation of COX-2 expression has been reported in cancer cells including malignant neural cancer and malignant peripheral nerve sheath tumor, and in response to inflammation and cell proliferation, it up-regulates prostaglandin synthases (34 -36). Thus, many studies on COX-2 as a target of drug development have been conducted (37,38). However, limited information concerning the function of COX-1, such as for the mucosal protection of the stomach and blood flow maintenance, has been available (39).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of COX-2 expression has been reported in cancer cells including malignant neural cancer and malignant peripheral nerve sheath tumor, and in response to inflammation and cell proliferation, it up-regulates prostaglandin synthases (34 -36). Thus, many studies on COX-2 as a target of drug development have been conducted (37,38). However, limited information concerning the function of COX-1, such as for the mucosal protection of the stomach and blood flow maintenance, has been available (39).…”
Section: Discussionmentioning
confidence: 99%
“…TECs were isolated, as described previously [17][18][19][20][21][22]. In a typical procedure, the TECs were isolated from OS-RC-2 tumors and dermal tissue in tumor-bearing mice using a magnetic cell sorting system (MACS; Milteny Biotec, Tokyo, Japan).…”
Section: Isolation Of Mouse Tumor Endothelial Cells (Tecs)mentioning
confidence: 99%
“…TECs from OS-RC-2 tumor tissue were successfully collected, as described previously [17][18][19][20][21][22]. As shown in Fig.…”
Section: Comparison Of Cytotoxicity In Tumor Cell and Tumor Endothelimentioning
confidence: 99%
“…However, there is no explicit information about the effects of non-steroidal anti-inflammatory drugs (NSAIDs) on the secretion of angiogenic growth factors (VEGF, bFGF) by normal endothelial cells. Many studies have reported antiangiogenic effects of cyclooxygenase COX-2 inhibitors on cancer cells (6). Among traditional NSAIDs, diclofenac is the strongest inhibitor of COX-2.…”
mentioning
confidence: 99%